IMMUNOMODULATORY EFFECT OF OYSTER GLYCOGEN ON ENDOMETRITIC CROSSBRED COWS - BISWAL, SHUVRANSHU SH; DASH, S; MOHANTY, D N (The Indian Journal of Animal Reproduction, 2023)
The purpose of the study was to evaluate the immunomodulatory effect of intrauterine infusion of oyster glycogen on endometritic cows. 500mg of oyster glycogen reconstituted in phosphate buffer saline (PBS) was given as intrauterine infusion to cows of group I (n=10) during estrus. In second group (n=10) normal estrus cows without any treatment formed as control. Cervical mucus sample was collected aseptically and sent to laboratory for bacterial culture and count.Polymorph nuclear (PMN) cell count from uterine fluid showed a significant elevation (13.14 ± 1.35vs.73.71 ± 3.59) before and after24hrs. of treatment. Serum globulin, albumin: globulin ratio, aspartate aminotransferase (AST), haptoglobin and serum amyloid A (SAA) values before treatment were significant (p<0.01) than in succeeding estrus after treatment.While serum total protein, albumin and ALT concentration doesn’t vary significantly (p<0.01 ). The conception rate in case of endometritis cows was 60 per cent after first post treatment insemination as compared to 70 per cent in normal cows. So it is concluded that oyster glycogen can be used as an effective immunomodulator as an alternative to antibiotic therapy.